Implantable slot antenna with substrate integrated waveguide for biomedical applications - Nik Abd Malik, Nik Noordini; Mohammed Jawad, Mustafa; Murad, Noor Asniza; Mohd Esa, Mona Riza; Ahmad, Mohd Riduan; Mekki, Anwer Sabah; Al-Dhief, Fahad Taha; Hussein, Yaqdhan Mahmood (Universitas Ahmad Dahlan, 2021)
This work presents a new design of capsule slot antenna with substrate integrated waveguide (SIW) for wireless body area networks (WBANs) operating at the range of (2.5-4 GHz) which is located in the body area networks (BAN) standard in IEEE802.15.6. The proposed antenna was designed for WBANs. The substrate is assumed to be from Rogers 5880 with relative permittivity of 2.2, and thickness of 0.787 mm. The ground and the patch are created from annealed copper while the capsule is assumed to be a plastic material of medical grade polycarbonate. The antenna designed and summited using computer simulation technology (CST) software. A CST voxel model was used to study the performance of SIW capsule antenna and the ability of the band (2.5-4 GHz). Results indicated a wide bandwidth of 1.5 GHz between the range of (2.5-4) GHz at 3.3 GHz as center frequency, with return loss with more than -24.52 dB, a gain of -18.2 dB, voltage standing wave ratio (VSWR) of 1.17, and front-to-back ratio (FBR) of 10.07 dB. Through simulation, all considerable parameters associated with the proposed antenna including return loss, bandwidth, operating frequency, VSWR less than 2, radiation pattern were examined. Regarding size, gain, and frequency band, the proposed antenna is located with the standards of implantable medical devices (IMDs).